Baseline retrobulbar blood flow is associated with both functional and structural glaucomatous progression after 4 years. Issue 3 (13th June 2016) - Moore, Nicholas A; Harris, Alon; Wentz, Scott; Verticchio Vercellin, Alice Chandra; Parekh, Priyanka; Gross, Joshua; Hussain, Rehan M; Thieme, Claudia; Siesky, Brent
Abstract : Background/aims: Previous studies suggest that vascular abnormalities are involved in the pathogenesis of open-angle glaucoma. This study aims to examine the relationship of baseline retrobulbar blood flow measurements with functional and structural glaucomatous progression in patients with open-angle glaucoma over 4 years. Methods: In this study, 112 patients with open-angle glaucoma were examined at baseline and 78 with retrobulbar blood flow assessments were followed to 4 years. Colour Doppler imaging was used to evaluate retrobulbar blood flow. Structural disease progression was examined with optical coherence tomography and Heidelberg Retinal Tomography III. Functional disease progression was monitored with automated perimetry using Humphrey visual fields. Mixed-model analysis of covariance was used to test for significance of changes from baseline to 4-year follow-up. Two-sample t tests and χ 2 tests were used to test for baseline blood flow differences between patients who progressed and those who did not progress. Results: Patients who progressed structurally had a statistically significant lower baseline mean ophthalmic artery peak systolic velocity (PSV) (p=0.024) and ophthalmic artery end diastolic velocity (EDV) (p=0.012) compared with those who did not progress. Similarly, a lower baseline mean ophthalmic artery PSV (p=0.031) and ophthalmic artery EDV (p=0.005) were associated with patients who progressed functionally compared with those who did not progress after 4 years. Conclusions: In this study population, lower baseline ophthalmic artery blood flow velocities were associated with simultaneous structural and functional glaucoma progression after 4 years.